Regional Trade Arrangements in Africa - Gupta, Sanjeev (International Monetary Fund, 2005)
In recent years, African policymakers have increasingly resorted to regional trade arrangements (RTAs) as a substitute for broad-based trade liberalization. This trend has long-term implications for the effectiveness of trade policy as a tool for poverty reduction and growth. This paper examines the record of RTAs in promoting trade and investment. It also explores policy measures that may help improve RTAs' performance.